Female Self Immolation A Field Study at the Kurdistan Region Level Erbil and Duhok Governorates as a Case Study - Shafiq, Ari Rafiq Shafiq (Sulaimani Journal for Humanities, 2026)
This study is an attempt to show and reveal the hidden and less obvious aspects of one of the family and social events, namely the events of (self burning women) in the Kurdistan Region, while the number of victims is increasing annually, who throw themselves from a high place, suicide with weapons, and bloody destruction. , is more common. The main goal of this study is to identify the motives, causes, and effects that lead them to light fire in their bodies with their hands. In this study, seven women were interviewed in both Erbil and Dohuk governorates. Five of the victims burned themselves, and two of the victims burned themselves in the same way as the victims who burned themselves, and they did not give any intentional reasons. At the end of the research, the field results were presented, which are the results of the hidden aspects captured from the interviews, and the general results of the research and statistics, which shed light on several laws and official decisions, and how to deal with suicide incidents.
Keywords: the situation; self burning; women